Comparison of Estimation Fetal Weight (EFW) using the Niswander Method and the Risanto Formula on Birth Weight - Dian Kusumaningtyas; Abkar Raden; Farida Kartini (Journal of Midwifery, 2022)
Fetal growth monitoring can be observed by measuring the Symphysis-Fundal Height (SFH). To determine fetal growth, the SFH measurement is calculated into the Estimation Fetal Weight (EFW) formula. EFW formulas using SFH measurements include the Niswander method and the Risanto formula. This study aims to compare the results of the calculation of the EFW formula which is closest to the birth weight of the baby. This study is a comparative descriptive study with a cross-sectional design, which measures the SFH and weighs the baby's birth weight directly. The population of this research is pregnant women who will give birth at RSUD Soewondo Kendal. A total of 176 samples were taken using a consecutive sampling technique. The results of the independent t-test showed that the Risanto formula had no difference in the birth weight of the baby, while the Niswander method had a significant difference in the actual birth weight of the baby.